Evaluation of the NG-Test MCR-1 Lateral Flow Assay and EDTA-Colistin Broth Disk Elution Methods To Detect Plasmid-Mediated Colistin Resistance among Gram-Negative Bacterial Isolates - Fenwick, Alexander J. (J Clin Microbiol, 2020)
Plasmid-mediated colistin resistance (PMCR) is a global public health concern, given its ease of transmissibility. The purpose of this study was to evaluate two methods for the detection of PMCR from bacterial colonies: (i) the NG-Test MCR-1 lateral flow immunoassay (LFA; NG Biotech, Guipry, France) and (ii) the EDTA-colistin broth disk elution (EDTA-CBDE) screening test method. These methods were evaluated using a cohort of contemporary, clinical Gram-negative bacillus isolates from 3 U.S. academic medical centers (126 isolates of the Enterobacterales, 50 Pseudomonas aeruginosa isolates, and 50 Acinetobacter species isolates; 1 isolate was mcr positive) and 12 mcr-positive CDC-FDA Antibiotic Resistance (AR) Isolate Bank isolates for which reference broth microdilution colistin susceptibility results were available. Eleven (4.6%) isolates were strongly positive by the MCR-1 LFA, with an additional 8 (3.4%) isolates yielding faintly positive results. The positive percent agreement (PPA) and negative percent agreement (NPA) for MCR-1 detection were 100% and 96.1%, respectively. Upon repeat testing, only a single false-positive MCR-2 producer remained, as the isolates with initially faintly positive results were negative. The EDTA-CBDE screening method had an overall PPA and NPA of 100% and 94.3%, respectively. The NPA for the EDTA-CBDE method was slightly lower at 94.2% with Enterobacterales, whereas it was 96.0% with P. aeruginosa. The MCR-1 LFA and EDTA-CBDE methods are both accurate and user-friendly methods for the detection of PMCR. Despite the rarity of PMCR among clinical isolates in the United States, these methods are valuable tools that may be implemented in public health and clinical microbiology laboratories to further discern the mechanism of resistance among colistin-resistant Gram-negative isolates and to detect PMCR for infection prevention and control purposes.